Advancing multiple-use water services for development in low- and middle-income countries - Stellenbauer, M; Jepson, W; Lefore, N; Thomson, P (Wiley, 2025)
Multiple-use water services (MUS) encompass a variety of water services that span the various livelihood strategies commonly seen in communities throughout low- and middle-income countries. MUS approaches can secure water for development, but limited peer-reviewed research comprehensively evaluates MUS. This review addresses a gap in the literature by tracing MUS as an international development strategy and evaluating the peer-reviewed scholarship published between 1990 and 2023 to describe the status and trends. The review identifies MUS attributes (e.g., water productivity, economics, health and nutrition, and gender empowerment) and the persistent barriers to scaling and institutionalization (e.g., regulatory and governance barriers and water quality). It then concludes with gaps in research (e.g., private sector roles and business models, ability to pay, ecosystem services, and climate resilience). MUS has the potential to be implemented tactically to address the nexus of water, food, nutrition, and water quality challenges, if research can contribute to evidence for scalable solutions that sufficiently address local needs.